(untitled) (Journal of Pathology of Nepal, 2012)
Background: Breast cancers rarely occur in young women but are known to have more aggressive behaviors and poorer outcome. We here compare the significance of breast carcinoma in female below the age of 35 to the age over 35 whose specimens were submitted to Manipal teaching hospital, Pokhara. Materials and Methods: All cases of mastectomy with carcinoma from January 2000 to September 2011 were included in the study. Clinical and histopathological datas of all cases were reviewed and collated. Results: A total of 148 mastectomy specimens were received, among which, 23 cases (16%) were below 35 years; whereas 125 cases (84%) were above 35 years of age. In both groups, Stage II was the commonest stage but stage III was much more common in older group (33% versus 9%) and stage I was more common in younger age group (39% versus 27%). Bloom Richardson grading showed that in the older age group, grade 1 is the commonest grade (50%) while in the younger group; grade 3 is the commonest (39%). Patients were followed for a varying period of 6 months to 5 years. Two cases (2% of followed up cases) in older group and 3 cases (15% of followed up cases) in the younger group showed recurrence. Conclusion: Breast carcinoma in the patients younger than 35 years though presented at an early stage has higher grade tumor and poorer outcome. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6021 JPN 2012; 2(3): 198-202